Pengembangan Panduan Peran dan Fungsi Top Manajer Keperawatan di Rumah Sakit - Asra Dewi; Rr. Tutik Sri Hariyati; Laurentia Dewi (Journal of Telenursing (JOTING), 2021)
This study aims to develop guidelines for the role and function of the head of the nursing field. This study method is a case study with a situation analysis. Data obtained through interviews and document study. The stages start from the assessment, problem identification, problem analysis, determination of problem priorities and making a plan of action. Implementation begins with the preparation of a draft guide and self-assessment, hiring expert, socialization and evaluation. This study is an innovation project that already has a permit from the Jakarta Hospital. The results showed that the role and function of the head of the nursing field has the potential to be improved. Innovations are developed by making guidelines and self-assessment referring to the literature covering three main managerial roles and five management functions. The trial of filling out self-assessment tools can be carried out. The conclusion of the roles and functions of the head of the nursing field is very important in supporting nursing governance and improving performance. Keywords: Nursing, Guidelines, Development, Management Roles and Functions, Top Managers